98.1k views
1 vote
7.89x10^-6+2.35x10^-8

User Rule
by
5.2k points

2 Answers

3 votes


7.89 * {10}^( - 6) + 2.35 * {10}^( - 8) = 7.9135 * {10}^( - 6)

User Chief Wiggum
by
5.5k points
2 votes


7.89 * 10^(-6) + 2.35 * 10^(-8) =

To add numbers in scientific notation, you need the exponents of 10 to be the same. We will convert the -8 to -6.


=7.89 * 10^(-6) + 2.35 * 10^(-2) * 10^(-6)


=7.89 * 10^(-6) + 2.35 * 0.01 * 10^(-6)


=7.89 * 10^(-6) + 0.0235 * 10^(-6)


=7.9135 * 10^(-6)

User Ilya Zinkovich
by
5.8k points